2021
DOI: 10.1002/1873-3468.14081
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of the plant N‐recognin ClpS1 and sequence determinants in its targets that govern substrate selection

Abstract: In the N‐degron pathway of protein degradation of Escherichia coli, the N‐recognin ClpS identifies substrates bearing N‐terminal phenylalanine, tyrosine, tryptophan, or leucine and delivers them to the caseinolytic protease (Clp). Chloroplasts contain the Clp system, but whether chloroplastic ClpS1 adheres to the same constraints is unknown. Moreover, the structural underpinnings of substrate recognition are not completely defined. We show that ClpS1 recognizes canonical residues of the E. coli N‐degron pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, Nt tyrosine was shown in yeast and Arabidopsis mitochondria to be removed by ICP55 and to be a destabilizing residue (Vogtle et al ., 2011; Carrie et al ., 2015; Huang et al ., 2015). In chloroplasts, binding of CLPS1 to Nt tyrosine is restricted and depends on the residue in the second position, that is, it is enhanced for YP (Aguilar Lucero et al ., 2021) but was not detected for YR (R, Arginine; Montandon et al ., 2019) but the impact of a neighboring S residue (as in the case observed here) is not known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Nt tyrosine was shown in yeast and Arabidopsis mitochondria to be removed by ICP55 and to be a destabilizing residue (Vogtle et al ., 2011; Carrie et al ., 2015; Huang et al ., 2015). In chloroplasts, binding of CLPS1 to Nt tyrosine is restricted and depends on the residue in the second position, that is, it is enhanced for YP (Aguilar Lucero et al ., 2021) but was not detected for YR (R, Arginine; Montandon et al ., 2019) but the impact of a neighboring S residue (as in the case observed here) is not known.…”
Section: Resultsmentioning
confidence: 99%
“…A second possibility is that the pathway via which improperly processed Nt proteoforms are normally removed by the peptidase network, in a quality control‐like mechanism, is blocked in peptidase mutants. This seems feasible; however, only few of the aberrant Nt proteoforms have plastid primary N‐degrons, such as phenylalanine, tyrosine, or tryptophan (Apel et al ., 2010; Carrie et al ., 2015; Rampello & Glynn, 2017; Bouchnak & van Wijk, 2019, 2021; Aguilar Lucero et al ., 2021; Kim et al ., 2021). A third possibility is that the limited precision of SPP under conditions of imbalanced proteostasis, folding stress and peptide fragment accumulation causes interference between substrates and SPP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We did evaluate for possible plastid N-degrons ( 5 , 68 ), and we observed three times a Leu (UVR3, HugZ-3, and DUF760-7) and once an Asp (UVR4) as the likely N-terminal residue. It was recently shown that N-terminal Leu is recognized by CLPS1 but that the following residue (the P2′ position) greatly affects the affinity, with Arg and also Gly enhancing the affinity but Leu, Ser, and Ala reducing affinity ( 68 ). Leu was followed by a Ser for HugZ-3 and DUF760-7 but Phe in case of UVR3.…”
Section: Resultsmentioning
confidence: 99%